Teachers’ perspective on challenges of substance abuse prevention among Malaysian secondary school students - Chan, Yuen Fook; Lim, Peck Choo; Gurnam Kaur Sidhu; Wee, Eng Hoe; Mohd. Zaiham Abd. Hamid (Penerbit UKM, 2015)
Substance abuse is a current and serious problem all around the globe. In fact, the number of substance abusers including school children and teenagers is growing. This study aims to identify challenges faced by secondary schools and the supports needed in the effort to curb substance abuse. A total of 18 high risk secondary schools were selected from Selangor, Wilayah Persekutuan Kuala Lumpur, Penang, Negeri Sembilan and Melaka. The questionnaire survey involved a total of 258 teachers from 18 selected schools. Data were analyzed descriptively using frequency counts and percentages. The results identifi ed the lack of student participation, time constraints and fi nancial problem as three main challenges in conducting drug prevention programmes in schools while the most crucial support needed by schools in organizing substance abuse programmes are material and fi nancial support, anti-drug talk/clinic and professional advice. It is recommended that substance abuse prevention programmes should involve the students’ families and the community to have better result. As for every substance abuse prevention programme held in schools, feedback from the participants should be obtained and analyzed in order to gauge the effectiveness and relevance of the programme. This study concluded that there are many challenges faced by schools in curbing substance abuse with lack of student participation, time constraints and fi nancial problem posed as the main challenges. Hence, involvement of all parties is needed to provide support needed to ensure the success of the implementation of substance abuse prevention programmes.